2018
DOI: 10.1029/2018gl079399
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Shelf Break Exchange Around the European Northwest Shelf

Abstract: Shelf seas act as a significant sink of carbon within the global ocean. This occurs as carbon is exported beneath the permanent oceanic thermocline through the downwelling circulation across the shelf break. This downwelling circulation is quantified here using two regional ocean model configurations of the European northwest shelf, with differing resolution (7‐ and 1.5‐km grid spacing). The dominant mechanisms and impact of model resolution are assessed along the length of the shelf break. The total downwelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 35 publications
5
35
0
1
Order By: Relevance
“…The heads of many canyons incise the edge of the NWES (Harris and Whiteway, 2011) and they are known to enhance shelf-edge exchange through advection and mixing, and can act as major conduits of dissolved and particulate matter from shallow to deep water (Allen and Durrieu De Madron, 2009;Puig et al, 2014). A recent study found that reducing the grid spacing in the AMM (Atlantic Margin Model) from 7 km to 1.5 km allowed smaller scale features such as canyons to be resolved, which contributed to stronger downwelling circulation in the higher resolution model (Graham et al, 2018). The models used here to estimate crossshelf exchange do not resolve submarine canyons and this is clearly a priority for future work.…”
Section: Outputs To Benthic Storage and The Open Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…The heads of many canyons incise the edge of the NWES (Harris and Whiteway, 2011) and they are known to enhance shelf-edge exchange through advection and mixing, and can act as major conduits of dissolved and particulate matter from shallow to deep water (Allen and Durrieu De Madron, 2009;Puig et al, 2014). A recent study found that reducing the grid spacing in the AMM (Atlantic Margin Model) from 7 km to 1.5 km allowed smaller scale features such as canyons to be resolved, which contributed to stronger downwelling circulation in the higher resolution model (Graham et al, 2018). The models used here to estimate crossshelf exchange do not resolve submarine canyons and this is clearly a priority for future work.…”
Section: Outputs To Benthic Storage and The Open Oceanmentioning
confidence: 99%
“…Models predict a weakening of the shelf edge current, especially in the eastward circulation in the northern North Sea (Holt et al, 2010;Tinker et al, 2016) and it is possible that this weakened circulation may reduce the strength of off-shelf carbon transport. However, recent work has highlighted that models with spatial resolutions of the order of 1 km are needed to resolve key processes controlling cross-shelf exchange (Graham et al, 2018), and there is a lack of suitable synoptic scale observations for verifying such models (Bôas et al, 2019).…”
Section: Changing Circulationmentioning
confidence: 99%
“…COAWST has also been implemented for a domain covering the north-west European shelf seas by Reza Hashemi et al (2015), similar to that used in this study, using a horizontal grid spacing of the order of 4 km (1/24 • ). Their analysis focused on the impact of coupling on the wave simulations for wave energy resource applications (Hashemi and Lewis, 2017). Lewis et al (2019) used the same COAWST system for the role of tidal dynamics on the wave climate of the Irish Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The simulated vertical profile of cross-shelf break transport during winter (DJFM) integrated along the 200 m isobath between 47 and 61.5 • N (Fig. 8a) shows the typical structure of a strong wind-driven on-shelf surface flow (0-40 m), an on-shelf flow in the interior of the water column (40-130 m) and an off-shelf Ekman drain at the bottom (130-200 m) due to basal stress of the slope current (Graham et al, 2018). Independent of the GIS melting rates, the net on-shelf winter transport through this section weakens under RCP8.5 by about 23 % (from 1.11 in 1971(from 1.11 in -2000(from 1.11 in to 0.86 Sv in 2101(from 1.11 in -2150.…”
Section: Changes In the Mean Ocean-shelf Nutrient Transportmentioning
confidence: 99%